Research and Practice of the Teaching of the "Marketing Planning" Course Based on the SPOC Flipped Classroom Model in China - Haien Quan; Yitong Den (International Journal of Education and Humanities, 2025)
In the era of "Internet +", the rapid development of digital technology has transformed the landscape of higher education in China. Various online learning platforms have emerged and become indispensable tools for teaching. However, the challenge lies in how to deeply integrate these technologies with traditional pedagogical models to enhance teaching quality and student engagement. This study addresses this challenge by focusing on the "Marketing Planning" course as a case study. The main objective is to develop and implement an innovative teaching model that bridges digital platforms and conventional teaching practices. The study begins by identifying the limitations of the original lecture-based approach, including low student engagement, lack of practical application, and minimal interaction. In response, the "Xuexitong" platform is adopted as a central tool, and a new teaching model is constructed, integrating Small Private Online Courses (SPOC), flipped classrooms, and project-based learning activities. The methodological approach involves redesigning course content, refining the implementation process, and restructuring the assessment system to foster active learning and continuous interaction. Results from pilot implementation indicate improved student participation, enhanced understanding of practical marketing skills, and more dynamic teacher-student interaction. The model fosters a synergistic online-offline teaching environment, placing students at the center of learning while positioning teachers as facilitators. It is recommended that similar integrative approaches be adopted across other management-related courses to drive teaching reform in higher education. The study offers a replicable framework for educators seeking to align traditional teaching with digital innovation under the "Internet +" paradigm